TANGGUNG JAWAB PENDIDIKAN PADA ANAK DALAM PERSPEKTIF ISLAM - Sulaiman, Muhammad; Abidin, Achmad Anwar (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Education is a fundamental right for human beings, especially for children. If ignored, there will be chaos in all aspects of life because of ignorance. In this article discussed the responsibility of education on the child, such responsibility is